Pelaksanaan UN Di Sumatera Barat: Persepsi Dan Harapan - Tri Kurniawati (PAKAR Pendidikan, 2014)
Indonesian government especially ministry of education conduct a policy called national test for the students as one way to improve the educational quality. But this policy get many arguments from stakeholders such as teachers, student, parents dan society. The aim of this research is to describe the perception and expectation of teachers in West Sumatera related to national test administration. As the results the tachers’ perception shows that national test administration in West Sumatera was relevant to the curriculum and be able to control the educational quality. But they also hope that in future the fund will be reported and managed transparantly. Based on this research, we recommend the goverment to improve teachers’ quality, and control the national test administration to avoid fraudulent.